A machine learning model for predicting serum neutralizing activity against Omicron SARS‐CoV‐2 BA.2 and BA.4/5 sublineages in the general population. Issue 4 (18th April 2023) - Camacho, Jorge; Albert, Eliseo; Álvarez‐Rodríguez, Beatriz; Rusu, Luciana; Zulaica, Joao; Moreno, Alicia Rodríguez; Peiró, Salvador; Geller, Ron; Navarro, David; Giménez, Estela
Abstract: Supervised machine learning (ML) methods have been used to predict antibody responses elicited by COVID‐19 vaccines in a variety of clinical settings. Here, we explored the reliability of a ML approach to predict the presence of detectable neutralizing antibody responses (NtAb) against Omicron BA.2 and BA.4/5 sublineages in the general population. Anti‐SARS‐CoV‐2 receptor‐binding domain (RBD) total antibodies were measured by the Elecsys® Anti‐SARS‐CoV‐2 S assay (Roche Diagnostics) in all participants. NtAbs against Omicron BA.2 and BA4/5 were measured using a SARS‐CoV‐2 S pseudotyped neutralization assay in 100 randomly selected sera. A ML model was built using the variables of age, vaccination (number of doses) and SARS‐CoV‐2 infection status. The model was trained in a cohort (TC) comprising 931 participants and validated in an external cohort (VC) including 787 individuals. Receiver operating characteristics analysis indicated that an anti‐SARS‐CoV‐2 RBD total antibody threshold of 2300 BAU/mL best discriminated between participants either exhibiting or not detectable Omicron BA.2 and Omicron BA.4/5‐Spike targeted NtAb responses (87% and 84% precision, respectively). The ML model correctly classified 88% (793/901) of participants in the TC: 717/749 (95.7%) of those displaying ≥2300 BAU/mL and 76/152 (50%) of those exhibiting antibody levels <2300 BAU/mL. The model performed better in vaccinated participants, either with or without prior SARS‐CoV‐2 infection. The overall accuracy of the ML model in the VC was comparable. Our ML model, based upon a few easily collected parameters for predicting neutralizing activity against Omicron BA.2 and BA.4/5 (sub)variants circumvents the need to perform not only neutralization assays, but also anti‐S serological tests, thus potentially saving costs in the setting of large seroprevalence studies.